Analysis of Productive Pedagogies of Pre-Service Teachers in Teaching Mathematics at School - Nurwati Djam'an; Bernard Bernard; Sahid Sahid; Sultoni Syukri (Didaktik Matematika, 2022)
This research aims to analyze the productive pedagogies of the pre-service teachers. Productive pedagogies are measured based on four dimension. This research involved three pre-service teachers in Universitas Negeri Makassar, Indonesia, who carry out teaching practices in schools. This research is a case study. The assessment of productive pedagogies was measured using a questionnaire, observation, and semi-structured interviews. The lowest average was found on the intellectual quality dimension of 79.6 (high category) based on the overall dimensions. This result suggests that, of all of the dimensions, Intellectual Quality was the least likely to be included in the classes. The highest dimension of the productive pedagogies of the pre-service teacher was connectedness, around 84.7, with a very high category. That means the pre-service teachers mainly focused on Connectedness during their teaching practice, followed by the Recognition of Differences around 82.2 (high category). Meanwhile, the Supportive Classroom Environment dimension is in the high category at about 79.9. Furthermore, for the Supportive Learning Environment dimension, two elements, academic engagement and self-regulation, were frequently observed in all pre-service teachers' classes. Still, student control, in which the teacher gives students chances to determine specific activities or outcomes of the lesson, was not very often.